Removal of thiazine dye azure a by sonolysis, sonophotolyisis , and sonocatalysis - Hassan A. Habeeb; Alaa T. Hamza (Al-Qadisiyah Journal of Pure Science, 2018)
This research is includes the efficiency of three methods of advanced oxidation processes and comparing them for decolonizing the textile dye Azure A in aqueous solution.These methods are ultrasound US only , ultrasound with ultraviolet (US / UV) and ultrasound with ozone (US / O3). The aim is to determine the best method of treatment for mineralization of colour . All the experiments have been done by using sonoreactor only , sonoreactor with photoreactor and sonoreactor with ozone . The study includes the investigating effects of dye concentration , temperature , pH, light intensity and air flow rate . Complete degradation has been achieved in a somewhat short time 60 min . The maximum removal of color was found in higher pH and temperature where at T=308K the removal percentage are 34%,60.2%,and 98% and at pH=8 are 33%,59.5%,and 97.6% by three methods consecution. shown the removal rate that increase withdecreases initial dye concentration , and also that the ratio of removal increases with rise of temperature , which decreases activated energy of reaction . It is noticed that activation energy value of removal dye are 13.8 , 9.95 , 8.15 KJ / mol at three methods successively . As far as pH is concerned , it appears that the ratio of removal decreased in acidic medium . Moreover , one can notice from the results with the increase of both air flow rate velocity and light intensity the ratio of removal increases . The decolonization reaction was found to follow first order kinetics with respect to the dye concentration